Mechanism of acid corrosion inhibition using magnetic nanofluid. (13th October 2016) - Parekh, Kinnari; Jauhari, Smita; Upadhyay, R V
Abstract: The inhibition effect of magnetic nanofluid  on carbon steel in acid solutions was investigated using gravimetric, potentiodynamic and SEM measurement. The inhibition efficiency increases up to 95% and 75% for 51.7 mM concentration, respectively, in 1 M HCl and 1 M H2 SO4 medium. The adsorption of nanoparticles to the steel surface forms a barrier between the metal and the aggressive environment, which is responsible for observed inhibition action. The adsorption of nanoparticles on steel surface is supported by the Langmuir and Freundlich adsorption isotherm and surface morphology scanned through SEM.